Unplanned pregnancies and reproductive health among women with bipolar disorder - Marengo, Eliana (2015)
Abstract Background The aim of this study was to investigate reproductive health and level of planning of pregnancies among women with bipolar disorder (BDW). Methods 63 euthymic women, with bipolar disorder type I, II or not otherwise specified diagnosis, were included and were matched with a control group of 63 healthy women. Demographic and clinical data, structured reproductive health measures and planning level of pregnancies were obtained and compared between groups. Results Lower level of planning of pregnancies and higher frequency of unplanned pregnancies were found among BDW. Women with bipolar disorder reported history of voluntary interruption of pregnancies more frequent than women from control group. Current reproductive health care showed no differences between groups. Limitations Data based on self-report of participants and retrospective nature of some collected measures may be affected by information bias. The pregnancy planning measure has not been validated in this population before. Demographic and clinical characteristics of the sample study limit generalization of these findings. Conclusions Adverse reproductive events, as unplanned pregnancies and elective interruption of pregnancies, may be more frequent among BDW. Clinician must be aware of the reproductive health during treatment of young BDW and take measures to improve better family planning access.